Peran Kementrian Agama Dalam Pembangunan Pendidikan Di Kabupaten Mandailing Natal - Lahuddin Rambe; Kholis Martua; Nur Ardila Rambe; Riska Pratama Tanjung; Nur Jannah Agriani (Dewantara : Jurnal Pendidikan Sosial Humaniora, 2024)
Vertical agencies of the Ministry of Religion are agencies within the Ministry of Religion that carry out the duties and functions of the Ministry of Religion in the regions. The vertical agencies of the Ministry of Religion consist of regional offices of the provincial Ministry of Religion and district/city offices of the Ministry of Religion. Development in the education sector is directed at "Improving Education Delivery Facilities", through improving the quality of education, curriculum development, improving educational supporting facilities and infrastructure, promotion and awards in the education sector, increasing the role of the community and stakeholders, as well as improving youth education.